Assessing adaptation options for climate change: A guide for coastal communities in the Coral Triangle of the Pacific 5. Social Network Analysis. - WorldFish (2013)
Assessing options for adapting to climate change is an important part of building resilient fishing and farming communities. This brochure is part of a series that collectively detail how a community-based assessment of climate change was used in partnership with coastal communities and provincial and national-level stakeholders in Timor-Leste and Solomon Islands. The assessment contains four distinct, but related, steps (Fig 1) focused on supporting community-level decision-making for adaptation through a series of participatory action research activities. Each brochure in this series details a specific activity in the four-step assessment. This series of eight brochures is primarily aimed for use where resources are limited or where it is more appropriate to use a rapid, qualitative and non-data intensive method of assessment. Community leaders, local NGOs and regional and national-level government representatives in developing countries may find this series useful. In this brochure we provide details of an activity relating to the ‘Evaluation of options’ step of the assessment, namely Social Network Analysis (SNA). This activity was conducted with community members and aimed at understanding the social networks that influence the capacity of fishers and farmers to produce food for consumption and cash sales. More specifically, the following questions were posed: • Who do fishers and farmers engage with in relation to their livelihood activities? • What are the resources that flow between different people and organizations (referred to as actors) in fisher and farmer social networks? • Who in the fisher and farmer social networks is important for enabling the implementation of adaptation options? Are the links to these actors effective and able to deliver the necessary resources? • Are there any actors missing from the social networks that would help improve effective implementation of adaptation actions and their sustainable use?